Given the unbalanced equation: ___Al2(SO4)3+___Ca(OH)2—>___Al(OH)3+__CaSO4
![Given the unbalanced equation Al2SO43CaOH2gtAlOH3CaSO4 class=](https://us-static.z-dn.net/files/d13/0b41490c2528632f9560060c0daef9d8.png)
Answer:
The answer to your question is letter B. 9
Explanation:
Unbalanced reaction
Al₂(SO₄)₃ + Ca(OH)₂ ⇒ Al(OH)₃ + CaSO₄
Reactants Elements Products
2 Al 1
3 S 1
14 O 7
1 Ca 1
2 H 3
Balanced reaction
Al₂(SO₄)₃ + 3Ca(OH)₂ ⇒ 2Al(OH)₃ + 3CaSO₄
Reactants Elements Products
2 Al 2
3 S 3
18 O 18
3 Ca 3
6 H 6
The sum of the coefficients is 1 + 3+ 2+ 3 = 9